Transformation and Existence of Pondok Pesantren to Face the Globalization of Education - Nur, Samsiah -; Bina, Rasyidin; Masyitah, Sri (Maharot : Journal of Islamic Education, 2023)
Pondok pesantren is an indigenous and traditional educational institution in Indonesia which is able to exists in this era with a myriad of challenges and competitiveness. This institution is strongly proven tocompete at recent time while keeping its Islamic values and characters. This article aims to investigate the process of transformation within the Pondok Pesantren, particularly Pesantren Ar-Raudlatul Hasanah Medan which is considered able to compete and adjust to the required system and development of education in Indonesia. This study applied qualitative approach with case study method by obtaining data from interview, observation and documentation. The results of the studyshowed that; 1) pesantren is able to transform from a traditional method of learning into Islamic formal education institution and it is recognized by the government from kindergarten school level up to higher education (university) while maintaining its pesantren system, 2) science and knowledge Islamisation without dichotomy between religious lessons and non-religious lessons (sciences) and technology, 3) the skill Human sources of Pesantren graduates are maintain a noble character able to contribute and serve the community in all regions. The result of the study concluded that Pesantren institution is able to synergize to face the challenge of recent era by develop potential and religious human resources.